Prevalence of Diabetes Among Out Patients in a Private Hospital - Daya, Edgardo (Journal of Education and Society, 2025)
A study on estimating the prevalence rate of Diabetes in an outpatient service of a hospital is one strategy to provide an estimated magnitude of this disease among those who visit the Hospital and measure their blood glucose levels either through Fasting Blood Sugar (FBS) or Glycosylated Hemoglobin (HbA1C). The study aims to estimate the prevalence of diabetes in an outpatient laboratory in a private hospital. A quantitative cross-sectional study was employed to answer the objective. Data from 300 patients’ samples were collected from the Laboratory Record which serves as the research instrument. The findings showed that (1) the prevalence of diabetes in the sampled cases is relatively high, (2) the FBS and HbA1C results were not affected or not associated with age and sex, and (3) the result of the estimate of high prevalence can already caution the hospital to do more preventive measures. The study recommends a comprehensive educational program for diabetes prevention, lifestyle modification and regular monitoring of blood glucose levels 3-4x a year is imperative. A future study possibly a prospective cohort study can be done including other factors that will affect the FBS and HbA1C results or in general, the prevalence of diabetes.